Entangled Borders - Sarah Green (Archivio Antropologico Mediterraneo)
If there is one thing that contemporary borders are supposed to do, it is to clearly separate things out, clearly demarcate the difference between here and somewhere else. It is obvious that this is not always, or perhaps even often, successfully achieved: the world is full of unfinished, contested and overlapping political borders. Drawing first from examples provided by the European Union and Brexit, and then from the past and present experiences of migration and the movement of peoples to and from the island of Lesvos, the paper suggests that understanding borders as being entangled, both with contemporary and past relations and separations from other places, can help in understanding contemporary border dynamics.